LATIHAN RESISTANCE BAND DAN SKIPPING : PENGARUH TERHADAP PENINGKATAN KEMAMPUAN SHOOTING SEPAK BOLA PERSEMAL - Masruddin Masruddin; Irsan Kahar; Septya Suarja (Jurnal Pendidikan Olah Raga, 2023)
Football is a popular sport in both developed and developing countries. The purpose of this study was to see if the shooting ability of Persemal soccer players could be significantly improved by using resistance bands and skipping exercises. In this study, total sampling is the sampling method used. In this study, the entire population of Persemal football players totaling 20 people was sampled. Therefore, this study belongs to the category of population studies. Bobby Charlton's shooting test was used to measure shooting ability in this study. Paired sample T-test and independent sample T-test are used in statistical data analysis. Paired sample T-tests showed that resistance band training had an average value of 0.000 on improving football shooting ability. In addition, skipping exercises have an average value of 0.000. So that the results of both exercises show that there is a significant influence on improving football shooting ability. The Independent Sample T-Test is used to compare and contrast the two exercises tested. The findings showed that no difference was seen between the two forms of exercise. Sig. pre-test score is 0.702 and post-test value is 0.600 respectively, higher than the required value of 0.05. As a result, it can be concluded that there is no significant difference between skipping training and resistance bands